2022
DOI: 10.2185/jrm.2022-025
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination uptake and adverse events following COVID-19 immunization in pregnant women in Northern India: a prospective, comparative, cohort study

Abstract: Objectives:The most commonly used vaccine in India, Covishield, is a recombinant adenovirus vector vaccine for which safety data in pregnant women are not available. The present study was conducted to assess the uptake of COVID-19 vaccines and monitor adverse events following COVID-19 immunization among pregnant women in northern India. Patients and Methods: A prospective cohort study was conducted among pregnant women registered with the antenatal clinics in Chandigarh Union Territory (U.T.) in northern India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…In our study, majority of the adverse events following COIVD-19 vaccination were reported within 1 day. Similar findings are also observed in the studies conducted by Goldshtein et al and Gandhi et al 8 , 25 It indicates that majority of the adverse events are either fever or injection site pain that are nearly similar with the routinely used pediatric or adult vaccines. The current study actively captured all events within 30 min after COVDI-19 vaccination among pregnant women, thereafter pregnant women passively report the adverse events experienced in the 30 days after vaccination.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our study, majority of the adverse events following COIVD-19 vaccination were reported within 1 day. Similar findings are also observed in the studies conducted by Goldshtein et al and Gandhi et al 8 , 25 It indicates that majority of the adverse events are either fever or injection site pain that are nearly similar with the routinely used pediatric or adult vaccines. The current study actively captured all events within 30 min after COVDI-19 vaccination among pregnant women, thereafter pregnant women passively report the adverse events experienced in the 30 days after vaccination.…”
Section: Discussionsupporting
confidence: 83%
“…Similar severe adverse events are also reported among 234 pregnant women vaccinated with Covaxin in Mumbai, India. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 16 studies (425 867 women) reporting SARS-CoV-2 infection-related outcomes6 7 17 19 21 31 33 36 38–45 and 35 (1 362 172 women) reporting pregnancy-related maternal and offspring outcomes in the secondary analysis 17 18 21–24 29–34 36 38 39 41–60. Twenty-three studies reported reactogenicity outcomes (94 206 women) following vaccination 38 39 46 61–80…”
Section: Resultsmentioning
confidence: 99%
“…Among the general population aged 45+ years in Tamil Nadu, a vaccination rate of 64% was reported between June–September 2021 19 ) . Among the general population in other parts of India, Arora et al and Dhumal et al reported that the uptake was 54.6% and 82.1%, respectively 20 , 21 ) , whereas Gandhi et al reported an uptake rate of 66.8% among pregnant women in Northern India 22 ) . However, the time interval between the present study and these studies was one year 19 , 20 , 21 ) .…”
Section: Discussionmentioning
confidence: 99%